Case 3792: Proposal to conserve current usage of Pachnaeus Schoenherr, 1826 by the suppression of Docorhinus Schoenherr, 1823 (Insecta, Coleoptera, Curculionidae) - Reily, Brian H; Franz, Nico M (Bulletin of Zoological Nomenclature)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve use of the generic name Pachnaeus Schoenherr, 1826 (CURCULIONIDAE, ENTIMINAE, EUSTYLINI). The name Pachnaeus is threatened by its senior objective synonym, Docorhinus Schoenherr, 1823, for which it was erroneously erected as a replacement name. Strict application of the Code would result in unnecessary confusion since the name Pachnaeus has been heavily used in the agricultural and taxonomic literature for the last 193 years, whereas its senior objective synonym Docorhinus has been treated as valid only once since it was (erroneously) replaced by Pachnaeus. Several members of Pachnaeus, for example Pachnaeus opalus (Olivier, 1807) (“northern citrus root weevil”, for which a lectotype is designated herein), Pachnaeus litus (Germar, 1824) (“southern citrus root weevil”), and Pachnaeus citri Marshall, 1916, are well documented and serious pests of citrus. Reverting the genus name to its senior synonym would lead to nomenclatural instability and confusion in the literature and, because of the singular treatment of Docorhinus as valid. Prevailing usage (Arts. 23.9.1 and 23.9.2) cannot be invoked to resolve this discrepancy. We therefore request a reversal of precedence under the Commission’s plenary power, with Docorhinus, the senior objective synonym, being suppressed.